THE CURRENT STATE AND TOPICAL ISSUES IN COGNITIVE LINGUISTICS - Saitmurotova Mokhira Rustam qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
Cognitive linguistics (CL) is an approach that views language deeply connected to human cognition and experience. The article explores the history and evolution of cognitive linguistics, its central hypotheses, and the contributions of key scholars such as Lakoff, Langacker, and Talmy. It highlights the foundational principles of CL, including the rejection of structuralist and generative theories. The article also examines core concepts such as conceptual metaphor theory, image schemas, and frame semantics, which have shaped the development of the field. Furthermore, it discusses how cognitive linguistics has developed into several trends, namely cognitive grammar, cognitive semantics, and cognitive stylistics.